Genetic variability and trait association under thrips (Megalurothrips sjostedti Trybom) infestation in cowpea (Vigna unguiculata [L.] Walp.) - Toyinbo, J.O.; Fatokun, C.; Boukar, O.; Fakorede, M.A.B. (Springer, 2021)
Flower bud thrips is one of the most destructive insect pests of cowpea in sub-Saharan Africa. Information on genetic variability among cowpea germplasm and interrelationships among traits under thrips infestation would facilitate the development of resistant varieties. The objectives of the study were to assess genetic variability for thrips resistance, estimate heritability of yield and other traits and investigate inter-trait relationships under thrips infestation. One hundred and fifty-six cowpea lines, including one resistant and one susceptible check, were screened for resistance under natural infestation at two locations in Nigeria, in 2016. Test lines were scored for thrips damage weekly for three consecutive weeks, after removal of spreader plants, to obtain damage scores (DS) 1, 2 and 3 while data were collected on agronomic traits. The data were subjected to analysis of variance from which genetic components of the phenotypic variance were computed. Interrelationships among traits were determined using phenotypic and genotypic correlation, and sequential path analyses. Significant variability was observed among test lines. Lines TVu 6824 and TVNu 1307 were identified as possessing thrips resistance. DS3 had significant genetic and phenotypic correlations with DS1, DS2 and yield-related traits. Number of pods per peduncle, number of peduncles per plant and DS3 were identified as first-order traits. Heritability estimates ranged from 0.55 to 0.73. Genetic variability among the lines suggests the possibility of genetic control of thrips while number of pods per peduncle, number of peduncles per plant and DS3 would serve as useful selection criteria for thrips resistance.